Dynamic heat transfer modeling of a closed refrigerated display cabinet. (October 2019) - Chaomuang, Nattawut; Laguerre, Onrawee; Flick, Denis
Highlights: A simplified heat transfer in transient state was developed for a closed display cabinet. A dynamic model allows the prediction of air and load temperature fluctuations. A spectral approach was used to solve the dynamic model. Estimation of load thickness whose temperature significantly fluctuates was presented. The dynamic model was able to predict temperature increase during defrosting. Abstract: This study proposes a simplified heat transfer model of a closed refrigerated display cabinet using a zonal approach. The dynamic model was developed and solved with a spectral method to predict the temperature fluctuations occurring with "on/off" compressor regulation. The equivalent load thickness in which the temperature fluctuations were of the same order as those at the load surface was estimated as a function of "on/off" compressor operating frequency. The air temperature fluctuations are dampened whenever the air exchanges heat with solid surfaces (e.g. walls, loads) and with the ambient air (e.g. through the doors). Despite exposure to large air temperature fluctuations (up to 5 °C), the load surface temperature showed only small fluctuations (ΔTl  ≤ 0.5 °C). Good agreement was found between the predicted and the measured temperature fluctuations. The model can also be applied in order to predict air and load temperature increases during defrost operation.